Cracking strut-and-tie model for shear strength evaluation of reinforced concrete deep beams. (15th May 2018) - Chen, Hui; Yi, Wei-Jian; Hwang, Hyeon-Jong
Highlights: A novel CSTM is developed to better predict the shear strength of RC deep beams. A simplified CSTM is also proposed for practical design. The validity of the CSTM is verified by 355 test specimens. Parametric analysis shows contribution of each shear mechanism on the shear strength. The CSTM describes well the effect of main design parameters on the shear strength. Abstract: In the present study, a novel cracking strut-and-tie model (CSTM) is developed to better predict the shear strength of a deep beam. The principal concept of strut-and-tie model (STM), the experimental phenomena of diagonal crack patterns, and strain distribution of longitudinal bars in shear span are considered. The proposed CSTM divides the diagonal strut into two parts according to the location of the critical shear crack (CSC). In the part above the CSC that is not affected by the flexural-shear cracks, its effective compressive strength is defined as the ultimate compressive strength of normal concrete strut. On the other hand, the effective compressive strength of the part below the CSC is derived from the forces transferred by the aggregate interlock, web reinforcement, and dowel action of longitudinal bars on the CSC surface. The improvement of aggregate interlock action under compression on the CSC surface, and the interaction between transverse reinforcement and longitudinal bars are theoretically considered. For practical design, a simplified CSTM is also proposed. The proposed method is applied to 355 existing test specimens, to predict the shear strength of deep beams with and without web reinforcement. The predicted results are compared with existing test results and the predictions of existing STMs. The results show that the prediction of the proposed model is better than those of other models. Further, parametric analysis is performed to evaluate the contribution of each shear mechanism. The analysis results show that the proposed CSTM is able to describe well the influences of main design parameters (i.e., shear span-to-depth ratio, longitudinal bar ratio, web reinforcement ratio, concrete compressive strength, and effective depth) on the shear resistance of deep beams.